Assessing the quality of universal basic education junior secodary school curricula as instruments for drop-out reduction in three core subjects in Lagos State. (2011)
The study assessed the quality of Universal Basic Education (UBE) Junior Secondary School (JSS) curricula as instruments for drop-out reduction in three core subjects in Lagos State. Seven quality indicators used were: comprehensiveness, application of teaching-learning methods and learning materials, responsiveness, relevance, opportunity to learn and adaptability. The study is an ex-post-factor research type. Four instruments: Mathematics, English language and Social Studies Teachers' Questionnaire respectively and Teacher Perception on Reduction of Students Dropping-out of School were used for the collection of relevant data. Multiple regression was used to analyse the data. The composite effects of the seven quality variables made strong and significant relation with students' drop-out reduction in mathematics, english language and social studies contributing (70%, 68% and 53% respectively). Adaptability was highly significant in explaining drop-out reduction in mathematics and social studies curricula whereas relevance was highly significant in english Language curriculum. Relevance made moderate significant effect on drop-out reduction in mathematics and english language curricula. Application of teaching-learning materials made significant negative explanatory effect on drop-out reduction in mathematics. In view of the inability of the current UBE core curricula to meet the quality criteria, an urgent review of these curricular is recommended among other things.